Cussac cave Gravettian parietal art (Dordogne, France): Updated inventories and new insights into Noaillian rock art. (August 2020) - Feruglio, Valérie; Bourdier, Camille; Aujoulat, Norbert; Delluc, Marc; Jaubert, Jacques
Highlights: The updated inventories of the bestiary are presented in terms of species frequency but also in terms of location. Technical, thematic, stylistic and iconographic analyses are presented. The rock art is consistent with the graphic repertoire of the Middle Gravettian, more precisely the Noaillian facies. Specific thematic and stylistic commonalities with sites from the Pyrenees and Basque Country are highlighted. The artistic expression at Cussac reveals a peculiar aspect of Noaillian culture in a restricted area of its general extension. Abstract: In 2008, the Collective Research Project funded by the French Ministry of Culture undertook the study of the decorated sepulchral cave of Cussac (Dordogne), discovered by Marc Delluc in 2000. In this paper, we present an update of Norbert Aujoulat's inventory (2001–2005), along with the results of a number of technical, thematic, stylistic and iconographic analyses. This examination confirmed that the rock art assemblage was both homogenous and consistent with the graphic repertoire of the Middle Gravettian (30, 500–28, 000 calBP), and more precisely the Noaillian facies. Specific thematic and stylistic commonalities with Gargas (French central Pyrenees) and the Basque Country were highlighted. For reasons of conservation and administrative restrictions, the study did not cover the entire cave, but what is referred to as the 'Downstream Branch' (the most densely decorated part of the cavity with most of the major panels, such as the Discovery Panel and the Grand Panel) and a long but incomplete portion of the 'Upstream Branch'. Rich as the site is, this analysis can provide archaeologists with important clues about the meaning of this exceptional site.